Fairness requires deliberation: the primacy of economic over social considerations - Hochman, Guy; Ayal, Shahar; Ariely, Dan (Frontiers in Psychology, 2015)
While both economic and social considerations of fairness and equity play an important role in financial decision-making, it is not clear which of these two motives is more primal and immediate and which one is secondary and slow. Here we used variants of the ultimatum game to examine this question. Experiment 1 shows that acceptance rate of unfair offers increases when participants are asked to base their choice on their gut-feelings, as compared to when they thoroughly consider the available information. In line with these results, Experiments 2 and 3 provide process evidence that individuals prefer to first examine economic information about their own utility rather than social information about equity and fairness, even at the price of foregoing such social information. Our results suggest that people are more economically rational at the core, but social considerations (e.g., inequality aversion) require deliberation, which under certain conditions override their self-interested impulses.